2005
DOI: 10.1081/cbi-200062410
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Chronic Sleep Onset Insomnia in Attention‐Deficit/Hyperactivity Disorder: A Circadian Rhythm Sleep Disorder

Abstract: To investigate whether ADHD-related sleep-onset insomnia (SOI) is a circadian rhythm disorder, we compared actigraphic sleep estimates, the circadian rest-activity rhythm, and dim light melatonin onset (DLMO) in ADHD children having chronic idiopathic SOI with that in ADHD children without sleep problems. Participants were 87 psychotropic-medication-naïve children, aged 6 to 12 yrs, with rigorously diagnosed ADHD and SOI (ADHD-SOI) and 33 children with ADHD without SOI (ADHD-noSOI) referred from community ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(142 citation statements)
references
References 38 publications
5
135
1
1
Order By: Relevance
“…142 Some patients with ADHD show a delayed sleep phase disorder. 143,144 In another study, a phase delay in the circadian rhythm of cortisol of adults with ADHD was found. 145 Other studies have observed a delay in the circadian rhythm of melatonin, as well as in the sleep-wake cycle, especially in ADHD patients who reported sleep onset insomnia.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…142 Some patients with ADHD show a delayed sleep phase disorder. 143,144 In another study, a phase delay in the circadian rhythm of cortisol of adults with ADHD was found. 145 Other studies have observed a delay in the circadian rhythm of melatonin, as well as in the sleep-wake cycle, especially in ADHD patients who reported sleep onset insomnia.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…8 Chronic sleep-onset insomnia has also been shown to be associated with childhood and adult ADHD. 9,10 ADHD is also associated with changes in diurnal preference towards greater eveningness. 4 The circadian clock is responsible for the generation of rhythms of behaviour and physiology on a near 24 period base, and has a key role in determining the rhythm of the sleep/wake cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal rhythms of melatonin secretion has been associated with childhood and adult ADHD. 9,10 Cortisol circadian profiles have been reported to be either unaltered in ADHD 12 or altered in association primarily with the hyperactive subtype of ADHD. 13,14 The molecular basis of such circadian rhythm generation consists of positive and negative transcriptional/translational feedback loops of 'clock' genes and their protein products, and single-nucleotide polymorphism in clock genes have been associated with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…21 This observation is consistent with the demonstrated delay in evening increases of endogenous melatonin levels in nonmedicated children with ADHD. 22 An evening circadian tendency is associated with both parental reports of sleep-onset delay and PSGmeasured sleep-onset latency in children with ADHD. 21 Consistent with these findings, melatonin has demonstrated efficacy for improving sleep-onset latency and total sleep time in 2 studies in this population.…”
Section: Discussionmentioning
confidence: 99%